Physical Interaction Of Chitosan-Alginate Entrapping Extract Of Papaya Leaf And Formation Of Submicron Particles Dosage Form - Untari, Budi; Wijaya, Dina Permata; Mardiyanto, Mardiyanto; Herlina, Herlina; Angraeni, Via; Firana, Ario (ARTS Publishing, 2019)
Research on physical interaction of chitosan-alginate entrapping extract of papaya leaf (Carica papaya L) into submicron particles formation has been performed. Preparation of papaya leaf extract into submicron particle dosage form of chitosan and sodium alginate polymer using ionic gelation method aimed to increase the solubility of extract. Submicron particles consisting of papaya leaf extract, chitosan, sodium alginate and CaCl2 were combined using variation of stirrer speed of 500, 750, and 1000 RPM. The optimum formula obtained has a speed of 1000 RPM with the percent EE value of 71.90%. The results of submicron particles characterization such as diameter and particle size distribution (PDI) using particle size analyzer (PSA) tools were 189.2 nm and 0.330. The results of XRD revealed the changes of type of crystalinity form to amorphous on submicron particles. The results of FTIR revealed the physical interaction without shifting of wave number of carbonyl, amine, and hydroxyl group which indicated that there were no chemical interactions occurred. These data indicated that papaya extract can be formulated into submicron particles of chitosan-alginate polymer.